Recovering images from traveltime data - (:unkn) unknown (My University, 2003)
The mathematical problem of recovering images from traveltime data was presented. The classical method of tomography provided information for reconstruction of function from a set of line integrals. The high and low speed anomalies were detected and their boundaries were recovered. The results proved that the method was a useful tool for retrieving slowness distribution from the traveltimes for the first arrivals.
Keywords: Inverse Problems; Nonlinear Integral Equations; Tomography